Sleep Disturbances Associated with Delirium in Conscious Patients in the Intensive Care Unit - Hana Locihová; Petr Matouch; Karel Axmann (Türk Yoğun Bakim Derneği Dergisi)
Objective: The primary aim of the study was to analyse the relationship between subjective sleep quality assessed with the numeric rating scale (NRS) and the presence of delirium identified with both the confusion assessment method for the intensive care unit (CAM-ICU) and intensive care delirium screening checklist (ICDSC). The secondary objective was to analyse the effect of other selected predictors on delirium. Materials and Methods: The prospective observational study included 126 non-intubated patients staying in the intensive care unit for more than 24 hours. Delirium was assessed simultaneously with both instruments (CAM-ICU and ICDSC) twice daily, and perceived sleep quality (NRS) was evaluated once a day. From 126 patients, 1299 paired questionnaires and 278 NRS records were obtained. Results: There were 37 (29.4%) and 40 (31.7%) patients identified as CAM-ICU positive or having an ICDSC score ≥4, respectively. An NRS ≤5 was found in 93 patients (73.8%). A statistically significant relationship between the incidence of delirium (assessed by two instruments) and sleep quality (NRS ≤5) was confirmed. The CAM-ICU positivity was 0.391 [95% confidence interval (CI), 0.36 to 0.421 (p<0.001)], and the ICDSC positivity was 0.463 [95% CI, 0.435 to 0.491 (p<0.001)]. This relationship strength (assessed using Kendall’s Tau) was rated as moderate. Conclusion: The study suggests a relationship between delirium and subjectively assessed sleep quality. In this respect, sleep disturbances are likely to contribute to the development of delirium, even without valid objective data confirming them as a definite risk factor.